Connect with a knowledgeable community and get your questions answered on IDNLearn.com. Our Q&A platform offers detailed and trustworthy answers to ensure you have the information you need.
Sagot :
To solve the equation [tex]\(\sin\left(\frac{\theta}{2}\right) = -\frac{1}{2}\)[/tex] over all real values of [tex]\(\theta\)[/tex], we proceed as follows:
1. Understand the basic trigonometric equation:
We start with [tex]\(\sin x = -\frac{1}{2}\)[/tex]. We know that sine is negative in the third and fourth quadrants. The reference angle for [tex]\(\sin x = \frac{1}{2}\)[/tex] is [tex]\(\frac{\pi}{6}\)[/tex], thus the solutions for [tex]\(\sin x = -\frac{1}{2}\)[/tex] are:
[tex]\[ x = -\frac{\pi}{6} + 2k\pi \quad \text{and} \quad x = \frac{7\pi}{6} + 2k\pi \][/tex]
for any integer [tex]\(k\)[/tex].
2. Apply the solutions to [tex]\(\sin\left(\frac{\theta}{2}\right)\)[/tex]:
Let [tex]\(x = \frac{\theta}{2}\)[/tex]. Substitute [tex]\(x\)[/tex] with [tex]\(\frac{\theta}{2}\)[/tex] in the general solutions:
[tex]\[ \frac{\theta}{2} = -\frac{\pi}{6} + 2k\pi \quad \text{and} \quad \frac{\theta}{2} = \frac{7\pi}{6} + 2k\pi \][/tex]
3. Solve for [tex]\(\theta\)[/tex]:
Multiply both sides of each equation by 2 to solve for [tex]\(\theta\)[/tex]:
[tex]\[ \theta = -\frac{\pi}{3} + 4k\pi \quad \text{and} \quad \theta = \frac{7\pi}{3} + 4k\pi \][/tex]
4. Rewrite the solutions:
Using [tex]\(n\)[/tex] as any integer (where [tex]\(n = k\)[/tex]):
[tex]\[ \theta = (-\frac{\pi}{3}) + 4n\pi \quad \text{and} \quad \theta = (\frac{7\pi}{3}) + 4n\pi \][/tex]
5. Additional equivalent form:
Noting that [tex]\(\frac{7\pi}{3}\)[/tex] can be expressed as [tex]\(\frac{4\pi}{3} + \pi\)[/tex], we get another commonly used form:
[tex]\[ \theta = (\frac{4\pi}{3}) + 4n\pi \][/tex]
Thus, the general solutions for [tex]\(\theta\)[/tex] are:
[tex]\[ \theta = (-\frac{\pi}{3}) + 4n\pi \quad \text{and} \quad \theta = (\frac{4\pi}{3}) + 4n\pi \][/tex]
So the correct multiple-choice answer is:
[tex]\[ \theta = \frac{7\pi}{3}, \frac{11\pi}{3} \][/tex]
1. Understand the basic trigonometric equation:
We start with [tex]\(\sin x = -\frac{1}{2}\)[/tex]. We know that sine is negative in the third and fourth quadrants. The reference angle for [tex]\(\sin x = \frac{1}{2}\)[/tex] is [tex]\(\frac{\pi}{6}\)[/tex], thus the solutions for [tex]\(\sin x = -\frac{1}{2}\)[/tex] are:
[tex]\[ x = -\frac{\pi}{6} + 2k\pi \quad \text{and} \quad x = \frac{7\pi}{6} + 2k\pi \][/tex]
for any integer [tex]\(k\)[/tex].
2. Apply the solutions to [tex]\(\sin\left(\frac{\theta}{2}\right)\)[/tex]:
Let [tex]\(x = \frac{\theta}{2}\)[/tex]. Substitute [tex]\(x\)[/tex] with [tex]\(\frac{\theta}{2}\)[/tex] in the general solutions:
[tex]\[ \frac{\theta}{2} = -\frac{\pi}{6} + 2k\pi \quad \text{and} \quad \frac{\theta}{2} = \frac{7\pi}{6} + 2k\pi \][/tex]
3. Solve for [tex]\(\theta\)[/tex]:
Multiply both sides of each equation by 2 to solve for [tex]\(\theta\)[/tex]:
[tex]\[ \theta = -\frac{\pi}{3} + 4k\pi \quad \text{and} \quad \theta = \frac{7\pi}{3} + 4k\pi \][/tex]
4. Rewrite the solutions:
Using [tex]\(n\)[/tex] as any integer (where [tex]\(n = k\)[/tex]):
[tex]\[ \theta = (-\frac{\pi}{3}) + 4n\pi \quad \text{and} \quad \theta = (\frac{7\pi}{3}) + 4n\pi \][/tex]
5. Additional equivalent form:
Noting that [tex]\(\frac{7\pi}{3}\)[/tex] can be expressed as [tex]\(\frac{4\pi}{3} + \pi\)[/tex], we get another commonly used form:
[tex]\[ \theta = (\frac{4\pi}{3}) + 4n\pi \][/tex]
Thus, the general solutions for [tex]\(\theta\)[/tex] are:
[tex]\[ \theta = (-\frac{\pi}{3}) + 4n\pi \quad \text{and} \quad \theta = (\frac{4\pi}{3}) + 4n\pi \][/tex]
So the correct multiple-choice answer is:
[tex]\[ \theta = \frac{7\pi}{3}, \frac{11\pi}{3} \][/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for visiting IDNLearn.com. We’re here to provide accurate and reliable answers, so visit us again soon.